Unequal gains from remote work during COVID-19 between spouses: Evidence from longitudinal data in Singapore. - Zeewan Lee; Poh Lin Tan; Jie-Sheng Tan-Soo (PLoS ONE)
The COVID-19 outbreak and the rise of remote work may have generated distinct labor market outcomes for workers, depending on their occupation and adaptability to changes in the mode of work. Using panel data of married spouses around the time of the government-mandated lockdown in Singapore and difference-in-differences models, we examine the effects of remote work arrangements on salary income, work hours, and wages. We find that the benefits of remote work during the pandemic were not distributed evenly across male and female spouses-translating into longer and significant gains in salary income only for male workers who adopted full remote work arrangements. In contrast, female remote workers' income gains were limited by disproportionately heavier household responsibilities (i.e., chores), which in turn led to constrained work hours.